Sanitation and Water for All : How Can the Financing Gap Be Filled? - World Bank Group (World Bank, Washington, DC, 2017)
For many countries still striving to provide their populations with basic access to water, sanitation and hygiene (WASH) services, the initial years of the Sustainable Development Goals (SDGs) is an appropriate time to reflect on and reassess current arrangements to finance the WASH sector. The 2017 High-Level Meeting of Finance Ministers will be the first held since the launch of the SDGs and will provide an opportunity for collective discussion on the roadmap for financing the water, sanitation and hygiene components of SDG 6, the so-called water SDG. The 2030 Agenda for Sustainable Development introduced a new level of ambition for water, sanitation and hygiene (WASH) services, encouraging countries to aspire to even higher levels of service and thus greater health, economic, social, and environmental benefits. This discussion paper provides a framework for country-level discussion, setting out key considerations for countries as they undertake financial planning for efforts to meet the SDGs. This paper covers the following aspects:(i) Estimating the costs and benefits associated with the SDG targets for WASH; (ii) Using existing financial resources more effectively; (iii) Accessing new resources; and (iv) Taking action to close the SDG financing gap.